Analysis of Phonological Errors in Reading Arabic Texts in Muhammadiyah Penggung Primary School Yogyakarta - Nurfitria Hidayati (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine phonological errors in reading Arabic texts for fifth grade students of SD Muhammadiyah Penggung. This research was conducted because there are still many errors found when reading Arabic, therefore researchers want to analyse phonological errors in consonants and vowels to evaluate and find solutions so that no more errors occur when reading Arabic texts. Arabic is very important to learn because it is part of the language of the Quran, so if errors continue to occur, it will result in errors in interpretation. This research uses descriptive qualitative research. The method used in this research is a case study. case study. The population in this study were fifth grade students at SD Muhammadiyah Penggung located in Kulon Progo with a total of 9 students. 9 students. The sampling technique used saturated sampling technique. where in the end the entire population was used as a sample. So, the sample in this study was 9 students. this study was 9 students. Then the data collection technique uses test and observation techniques. documentation techniques. observation techniques. The results of this study showed that phonological errors were found when fifth grade students at SD Muhammadiyah Penggung read Arabic texts. The errors are found in consonants and vowels. For errors in consonants, 16 errors were found. Then 19 errors were found in vowel errors.